OPTIMASI WAKTU PENGUKUSAN PRESTO KEPITING BAKAU (Scylla serrata) DENGAN ALAT â€SOFT CRAB PRESTOâ€ - somat, ridho; darmanto, ys; riyadi, putut har (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Mangrove crab is a crab that has commercial value and potential to be developed because themeat is delicious and high protein content. The purpose of the research is to determine theoptimum cooking time for crab presto obtained with the expected quality and to know thequality of crab presto with the variation in cooking time. The result showed that the best timeused for cooking presto crabs using Soft Crab Presto is 90 minutes. The highest value basedon organoleptic test are appearance 7.7, odor 7.9 and texture 8.0 during 60 minutes cooking.The best value brittleness of the shells is 1647.93 gF in 90 minutes of cooking time. Whilechemical testing on the crab presto showed 79.08% moisture content during 60 minutescooking, 14.66% protein content during 60 minutes cooking, the fat content is 0.649% at 60minutes of cooking time.